Causes of death in people with coeliac disease in England compared with the general population: a competing risk analysis. Issue 8 (24th October 2014) - Abdul Sultan, Alyshah; Crooks, Colin J; Card, Tim; Tata, Laila J; Fleming, Kate M; West, Joe
Abstract : Introduction: Quantifying excess cause-specific mortality among people with coeliac disease (CD) compared with the general population accounting for competing risks will allow accurate information to be given on risk of death from specific causes. Method: We identified from the Clinical Practice Research Datalink all patients with CD linked to Office for National Statistics between 1998 and 2012. We selected controls by frequency matching from the registered general practice population within 10-year age bands. We calculated the adjusted cumulative incidence (including adjustment for competing risks) and excess cumulative incidence for different causes of death up to 10 years from diagnosis. Results: Of the 10 825 patients with CD, 773 died within the study period. The overall mortality rate among patients with CD was 128/10 000 person years compared with 153/10 000 in controls (HR=0.94 95% CI 0.84 to 1.01). We found no overall difference in the cumulative incidence of respiratory disease, digestive disease or cancer related death among cases and controls. The adjusted cumulative incidence of death from cardiovascular deaths was slightly lower compared with those without CD diagnosis (CD 0.32% vs controls 0.41%) with a corresponding excess cumulative incidence of −0.08% (95% CI −0.13 to −0.04). However, patients with CD had 0.15% excess risk (95% CI 0.03 to 0.27) of deaths from non-Hodgkin's lymphoma from the general population baseline risk. Conclusions: Overall, people with CD have no major excess risk of cancer, digestive disease or respiratory disease related or cardiovascular mortality compared with the general population. These findings should be reassuring to patients with CD and clinicians managing their care.